2005
DOI: 10.1203/01.pdr.0000155759.29448.13
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Peripheral and Cord Blood Mononuclear Cells Altered by Thymic Stromal Lymphopoietin

Abstract: Thymic stromal lymphopoietin (TSLP) was reported to induce dendritic cells to produce Th2-attracting chemokines, followed by allergic inflammation through stimulating not only CD4-positive T cells but also CD8-positive T cells. Therefore, in this experiment, GeneChip and hierarchical clustering were applied to screen the molecules in whole immunity triggered by TSLP directly and indirectly using both adult peripheral and cord blood mononuclear cells as well as isolated monocytes. Gene expression profiles scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition to its overlapping effects with IL‐13 and TGFβ on gene expression, TSLP induced a distinct set of genes in murine skin, including CXCL9, a gene whose expression we had previously shown is increased in SSc skin (14). We showed that TSLP also induces CXCL9 by PBMCs in vitro, consistent with the results of a previous study where high levels of proteasomes, chemokines including CXCL9, and IL‐13–regulated genes were observed in PBMCs stimulated with TSLP (27). We showed that TSLP rapidly stimulates proinflammatory gene expression by PBMCs followed by induction of a more profibrotic marker, MRC1.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to its overlapping effects with IL‐13 and TGFβ on gene expression, TSLP induced a distinct set of genes in murine skin, including CXCL9, a gene whose expression we had previously shown is increased in SSc skin (14). We showed that TSLP also induces CXCL9 by PBMCs in vitro, consistent with the results of a previous study where high levels of proteasomes, chemokines including CXCL9, and IL‐13–regulated genes were observed in PBMCs stimulated with TSLP (27). We showed that TSLP rapidly stimulates proinflammatory gene expression by PBMCs followed by induction of a more profibrotic marker, MRC1.…”
Section: Discussionsupporting
confidence: 91%
“…These minimal morphological changes have been associated with significant fetal PBMC response to maternal obesity in our study. Urashima et al [54] showed differences in gene expression between adult and fetal PBMC. In agreement with that data, we found that the response of fetal PBMC included 27 significantly changed pathways while in mothers 10 pathways differed.…”
Section: Discussionmentioning
confidence: 99%
“…We have applied this approach to the fields of oncology [9][10][11] and immunology [12] . In previous works on neurology, gene expression profiling was used in rodent models of transient middle cerebral artery occlusion (MCAO) [13,14] ; results elucidated many genes associated with transient cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%